Mechanisms of resentment : causes of social intolerance and anti-democratic attitudes in Europe - Salomo, Katja (2021)
The thesis attempts to identify social mechanisms that connect different forms of resentment – intolerance towards social minorities, anti-democratic views, electoral radical right-wing support – to (changes in) the social and demographic structure of society, economic conditions, policies, and party politics set against the specific historic backgrounds of European countries. “Radical Right-Wing Support among Urban Voters” investigates how immigration into cities – where most immigrants into European countries tend settle – increases electoral radical right-wing support, in the context of poverty, residential segregation and the history of immigration into neighborhoods. The analysis makes use of unique contextual data on neighborhoods in 34 German cities between the years 2014–2017 enriched with election data. “The Residential Context as Source of Deprivation” investigates the political rural–urban divide in current democracies: In regions exposed to precarious demographic developments – heavy emigration, aging populations, few children, skewed adult sex ratios – shops, services, events, and transportation infrastructure thin out, social support systems suffer, and so on, leaving residents feeling disadvantaged. In worldwide comparison, East Germany is more strongly affected by these demographic developments than any other region. The study uses an yearly East-German survey covering the years 2000–2014 enriched with regional contextual data to show long-term effects of demographic developments on anti-immigrant and nationalist attitudes as well as on democratic discontent. “Dynamics of Immigrant Resentment in Europe” focuses on differences between countries by undertaking the first comprehensive test of all social explanations of immigrant resentment predominant in the research literature across 30 European countries between the years 2002–2016, relying on the European Social Survey and comprehensive contextual data